The Microbiologist's Guide to Membrane Potential Dynamics. Issue 4 (April 2020) - Benarroch, Jonatan M.; Asally, Munehiro
Abstract : All cellular membranes have the functionality of generating and maintaining the gradients of electrical and electrochemical potentials. Such potentials were generally thought to be an essential but homeostatic contributor to complex bacterial behaviors. Recent studies have revised this view, and we now know that bacterial membrane potential is dynamic and plays signaling roles in cell–cell interaction, adaptation to antibiotics, and sensation of cellular conditions and environments. These discoveries argue that bacterial membrane potential dynamics deserve more attention. Here, we review the recent studies revealing the signaling roles of bacterial membrane potential dynamics. We also introduce basic biophysical theories of the membrane potential to the microbiology community and discuss the needs to revise these theories for applications in bacterial electrophysiology. Highlights: Bacterial membrane potential is dynamic, with the ability to hyperpolarize and depolarize. The dynamics of bacterial membrane potential mediate signaling at the single-cell and biofilm levels. Bacterial electrophysiology is different from neural electrophysiology because of the size of bacteria and their membrane structure. Techniques have been developed and utilized to measure bacterial membrane potential quantitatively and temporally.